Activation of Secondary Metabolite Gene Clusters in Streptomyces clavuligerus by the PimM Regulator of Streptomyces natalensis - Martínez-Burgo, Yolanda; Santos-Aberturas, Javier; Rodríguez-García, Antonio; Barreales, Eva G.; Tormo, José Rubén; Truman, Andrew W.; Reyes, Fernando; Aparicio, Jesús F.; Liras, Paloma (Frontiers in Microbiology, 2019)
Expression of non-native transcriptional activators may be a powerful general method to activate secondary metabolites biosynthetic pathways. PAS-LuxR regulators, whose archetype is PimM, activates the biosynthesis of polyene macrolide antifungals and other antibiotics, and have been shown to be functionally preserved across multiple Streptomyces strains. In this work we show that constitutive expression of pimM in S. clavuligerus ATCC 27064 significantly affected its transcriptome and modifies secondary metabolism. Almost all genes in three secondary metabolites clusters were overexpressed, including the clusters responsible for the biosynthesis of the clinically important clavulanic acid and cephamycin C. In comparison to a control strain, this resulted in 10- and 7-fold higher production levels of these metabolites, respectively. Metabolomic and bioactivity studies of S. clavuligerus::pimM also revealed deep metabolic changes. Antifungal activity absent in the control strain was detected in S. clavuligerus::pimM, and determined to be the result of a 5-fold increase in the production of the tunicamycin complex.